Investigating the traffic-related environmental impacts of hydraulic-fracturing (fracking) operations. (April 2016) - Goodman, Paul S.; Galatioto, Fabio; Thorpe, Neil; Namdeo, Anil K.; Davies, Richard J.; Bird, Roger N.
Abstract: Hydraulic fracturing (fracking) has been used extensively in the US and Canada since the 1950s and offers the potential for significant new sources of oil and gas supply. Numerous other countries around the world (including the UK, Germany, China, South Africa, Australia and Argentina) are now giving serious consideration to sanctioning the technique to provide additional security over the future supply of domestic energy. However, relatively high population densities in many countries and the potential negative environmental impacts that may be associated with fracking operations has stimulated controversy and significant public debate regarding if and where fracking should be permitted. Road traffic generated by fracking operations is one possible source of environmental impact whose significance has, until now, been largely neglected in the available literature. This paper therefore presents a scoping-level environmental assessment for individual and groups of fracking sites using a newly-created Traffic Impacts Model (TIM). The model produces estimates of the traffic-related impacts of fracking on greenhouse gas emissions, local air quality emissions, noise and road pavement wear, using a range of hypothetical fracking scenarios to quantify changes in impacts against baseline levels. Results suggest that the local impacts of a single well pad may be short duration but large magnitude. That is, whilst single digit percentile increases in emissions of CO2, NOx and PM are estimated for the period from start of construction to pad completion (potentially several months or years), excess emissions of NOx on individual days of peak activity can reach 30% over baseline. Likewise, excess noise emissions appear negligible (< 1 dBA) when normalised over the completion period, but may be considerable (+ 3.4 dBA) in particular hours, especially in night-time periods. Larger, regional scale modelling of pad development scenarios over a multi-decade time horizon give modest CO2 emissions that vary between 2.5 and 160.4 kT, dependent on the number of wells, and individual well fracking water and flowback waste requirements. The TIM model is designed to be adaptable to any geographic area where the required input data are available (such as fleet characteristics, road type and quality), and we suggest could be deployed as a tool to help reach more informed decisions regarding where and how fracking might take place taking into account the likely scale of traffic-related environmental impacts. Highlights: Traffic-related environmental impacts of fracking studied using a novel Traffic Impact Model. Model estimates greenhouse gas, local air quality, noise and axle loading impacts on roads. Single well pad creates substantial increases in local air quality pollutants during peak activity. Short-duration/large-magnitude events may adversely affect local ambient air quality and noise. Daily NOx emissions may increase by over 30% and hourly noise levels can double (+ 3.4 dBA)